IoT-Based Cup Sealer Machine Automation Using Nodemcu ESP32 - Nur Aminudin; Budi Usmanto; Dwi Feriyanto; Dita Septasari; Tahta Herdian Andika; Adamu Abubakar Muhammad (CV Media Inti Teknologi, 2025)
Background of study: The development of the food and beverage industry demands innovation in efficient and reliable packaging processes. Conventional cup sealing machines often face limitations in speed and precision, necessitating technology-based solutions. Aims and scope of paper: This objective of the study is to design and implement an automated cup sealer system based on the Internet of Things (IoT), using the NodeMCU ESP32, capable of performing sealing and real-time monitoring. The system integrates a flowmeter sensor to detect the presence of cups, a stepper motor for the sealing process, and an LCD display along with WiFi connectivity for monitoring production data. Methods: The methodology involves hardware design, control system programming, and performance testing of the device under various temperature and motor speed parameters. Result: The results show that the system can increase production efficiency by up to six times compared to the manual method, with a capacity of 300 cups per hour and a sealing success rate of 95% at an optimal temperature of 100°C and a motor speed of 10 RPM. Synchronization among components was enhanced through sensor calibration and algorithm development. Conclusion: In conclusion, this automated system not only improves efficiency and accuracy but also offers flexibility and IoT-based control, making it highly relevant for small and medium-sized industries.